Inconsistency in Circulating Irisin Levels: What is Really Happening? - Sanchis-Gomar, F.; Alis, R.; Pareja-Galeano, H.; Romagnoli, M.; Perez-Quilis, C. (Hormone and Metabolic Research, 2014)
The discovery of irisin as a novel and promising peptidic hormone for the treatment of obesity and diabetes has recently been reported. As a result, great hopes have been raised based on this finding, hypothesizing that irisin might provide additional benefits, not only for obesity and diabetes, but also for a wide range of pathological conditions requiring therapeutical and clinical attention. However, controversial results and conclusions on circulating irisin concentrations and correlations with other variables, including its role in metabolism, have recently been reported. Although laboratory assessment of irisin by ELISA is easily available and may provide interesting information for therapeutics and clinical practice, the heterogeneous and often discrepant results published so far, raise serious concerns about its measurement, indicating that it may still not be ready for use or whether irisin really exists. We highlight here some aspects on these discrepancies and contradictions, and put forward their implications.
Keywords: myokine; hormone; diabetes; obesity; metabolic syndrome